Impact of Aortic Tortuosity on Displacement Forces in Descending Thoracic Aortic Aneurysms. (April 2020) - Belvroy, Viony M.; Romarowski, Rodrigo M.; van Bakel, Theodorus M.J.; van Herwaarden, Joost A.; Bismuth, Jean; Auricchio, Ferdinando; Moll, Frans L.; Trimarchi, Santi
Abstract : Objective: As elastin fibres in the aorta deteriorate with age, the descending thoracic aorta (DTA) becomes longer and more tortuous. In patients with DTA aneurysms, this increased tortuosity may result in a hostile haemodynamic environment for thoracic endovascular aortic repair (TEVAR). The objective of this study was to analyse how increased tortuosity affects haemodynamic displacement forces (DFs) in different segments of the DTA in patients with DTA aneurysms (DTAAs). Methods: Thirty patients with DTAAs were selected to form three equal groups based on the maximum tortuosity of their DTA: low < 30°, moderate 30°–60°, and high > 60°. Computational fluid dynamics simulations were performed to calculate DFs in all patients. Image based segmentations were carried out to create patient specific models of the aortic geometry. When physiological simulation results were obtained, the haemodynamic DFs on the aortic wall were calculated in four segments of the DTA (zones 4A – D). To enable comparison of DFs in different segments, the DF was normalised by the aortic wall surface area, the equivalent surface traction (EST). Results: The mean age was 73 years, with 67% male. In zone 4C, where most tortuosity occurs, the EST in patients with high tortuosity was more than three times higher, than those with low tortuosity (low, 743 N/m 2 ; moderate, 956 N/m 2 ; high, 2294 N/m 2 ; p = .004). These differences could be attributed to the higher sideways components of the DF vectors, which were more than two times greater in patients with high tortuosity than in patients with low or moderate tortuosity (low, 5.01 N; moderate, 5.50 N; high, 13.21 N; p = .009). Conclusion: High tortuosity results in increased displacement forces in the distal segments of the DTA. These forces should be taken into account when planning for TEVAR, as potentially they increase the risk of stent graft related complications, such as migration and endoleak.